2013
DOI: 10.3390/ijerph10030856
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Unsupervised Bathing of Infants: A Cross-Sectional Study

Abstract: Drowning represents the third leading cause of fatal unintentional injury in infants (0–1 years). The aim of this study is to investigate correlates of unsupervised bathing. This cross-sectional study included 1,410 parents with an infant. Parents completed a questionnaire regarding supervision during bathing, socio-demographic factors, and Protection Motivation Theory-constructs. To determine correlates of parents who leave their infant unsupervised, logistic regression analyses were performed. Of the parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…To improve parents’ child safety behaviors, various cognitions (eg, perceived self-efficacy, perceived response efficacy, perceived vulnerability, and perceived severity) could be addressed [ 51 - 53 ]. Changing these cognitions about injury prevention behavior could possibly lead to more safe behavior.…”
Section: Discussionmentioning
confidence: 99%
“…To improve parents’ child safety behaviors, various cognitions (eg, perceived self-efficacy, perceived response efficacy, perceived vulnerability, and perceived severity) could be addressed [ 51 - 53 ]. Changing these cognitions about injury prevention behavior could possibly lead to more safe behavior.…”
Section: Discussionmentioning
confidence: 99%
“…34 Of note, first-time parents were less likely to leave children in the bathtub when compared with parents with an older child. 36 The association of unsupervised bathtub drowning deaths with the use of bathtub seats and rings was recognized more than 2 decades ago. 37 The bath seat and ring are designed to position the infant in a sitting position with 3 to 4 legs and suction cups at their base.…”
Section: Settingmentioning
confidence: 99%
“…American Academy of Pediatrics recommended that children under the age of five are not supposed to be left alone in the bathroom even for a short duration [14] . Previous studies showed lower prevalence of mothers who allowed their children to bathe alone [13], [15] . The possible reason were, the age group of children and specific cases of drowning injury who presented to the emergency department [15], [13] .…”
Section: Discussionmentioning
confidence: 89%
“…The possible reason were, the age group of children and specific cases of drowning injury who presented to the emergency department [15], [13] . The perception of mothers towards the benefit of supervision determined their practices [15] .…”
Section: Discussionmentioning
confidence: 99%